Coal Supply Chain Management and Economic Efficiency of using High-Ash Coking Coal in Ferroalloy Manufacturing - Akhmetzhanov, Bura; Tazhibekova, Kashamida; Shametova, Aigerim; Urazbekov, Abay (International Journal of Supply Chain Management, 2019)
In the global competitive environment, metallurgical industries reach progress through cuts in production costs. In this light, the priorities to boost ferroalloy manufacturing include the effective innovative material- and energy-saving technologies, which are applied to alternative carbonaceous reducing agents used in ferroalloy production. Additionally to a regression model for predicting the average annual world prices for steel, this article assesses the economic efficiency of using weak coking coals in ferroalloy manufacturing. This study also explores the relationship between supply chain management and production cost considered a key factor in supply chain management. The factors influencing price behaviour are the capacity of the world metallurgical plants and the price for coking coal. The economic efficiency of using high-ash coking coal to produce ferroalloys was studied on the ferrosilicoaluminium (FeSiAl) FS55A20 against the ferrosilicon FS75. The comparative analysis was performed using economic-mathematical modelling. The commercial efficiency of investment projects was studied using statistical (payback period) and dynamic (net present value) methods. Based on these factors, the steel price forecast was made for 2019–2023. In ferroalloy manufacturing, the shift from ferrosilicon FS75 to ferrosilicoaluminium FS55A20 will bring a profit of USD 2.1 million annually. The average payback period for investments in the project was 2 years. The calculated net present value of the project was USD 2.4 million. The analysis resulted in the outline of the main factors to consider when choosing a strategy of supply chain management.